Review of Islamic Law and Trade Regulations on the Practice of Buying and Selling Imported Used Clothes - Muchtar, Amar; Wargo, Wargo; Kurniawan, Kurniawan (CV. Zabags Qu Publish, 2025)
This study aims to examine the practice of buying and selling imported used clothes at the West Sabak Main Market from the perspective of Islamic law and Regulation of the Minister of Trade of the Republic of Indonesia Number 40 of 2022. This study uses a qualitative approach with descriptive-normative and empirical methods. Data were collected through interviews and documentation studies. The results of the study show that the practice is still active even though it violates official regulations. In the view of Islamic law, the buying and selling of used clothes is allowed as long as it meets the conditions of the validity of the contract and does not bring harm. However, violations of positive law can be categorized as a prohibited form of ta'addi. Therefore, it is important to have legal education and guidance from religious leaders and authorities so that trade practices remain in accordance with sharia and state regulations.